Developing Nearpod-based interactive learning media on the topic of algebra to improve critical thinking ability - Dian Kurniati; Sabna Setiawati; Dhanar Dwi Hary Jatmiko; Arika Indah Kristiana; Rafiantika Megahnia Prihandini (AXIOM : Jurnal Pendidikan dan Matematika, 2026)
Interactive learning has become a necessity in the modern educational era, particularly for facilitating students’ understanding of abstract mathematical concepts such as algebra. Difficulties in comprehending algebraic concepts often hinder the development of students’ critical thinking skills, which are essential for solving problems and making logical decisions. This study aimed to develop Nearpod-assisted interactive learning media and examine its effectiveness in enhancing students’ critical thinking skills in algebra. The study employed the Thiagarajan (4-D) development model, consisting of four stages, namely define, design, develop, and disseminate. The research subjects were selected through purposive sampling and consisted of 31 seventh-grade students (16 females and 15 males) from Class VII G of State Junior High School 4 Jember, Indonesia, who demonstrated low levels of critical thinking skills based on the results of an initial assessment. Data were collected through classroom observations, critical thinking tests, and student response questionnaires. The effectiveness of the developed media was evaluated by testing the research hypothesis regarding the impact of Nearpod-assisted learning on students’ critical thinking skills. Data were analyzed using a paired-samples t-test and N-Gain analysis. The t-test results showed a significance value (Sig. 2-tailed) of 0.000 (< 0.05), indicating a significant difference between the mean pre-test and post-test scores. Furthermore, the N-Gain percentage reached 80.19%, indicating a high level of improvement. These findings suggest that Nearpod-assisted interactive learning media is effective in improving students’ critical thinking skills in algebra and positively contributes to their learning outcomes at State Junior High School 4 Jember.